Mucosal Challenge Ferret Models of Ebola Virus Disease - Trevor Brasel; Jason E. Comer; Shane Massey; Jeanon Smith; Jennifer Smith; Matthew Hyde; Andrew Kocsis; Melicia Gainey; Nancy Niemuth; Cheryl Triplett; Thomas Rudge (Pathogens, 2021)
Recent studies have shown the domestic ferret (Mustela putorius furo) to be a promising small animal model for the study of Ebola virus (EBOV) disease and medical countermeasure evaluation. To date, most studies have focused on traditional challenge routes, predominantly intramuscular and intranasal administration. Here, we present results from a non-clinical pathogenicity study examining oronasal, oral, and ocular mucosal challenge routes in ferrets. Animals were challenged with 1, 10, or 100 plaque forming units EBOV followed by monitoring of disease progression and biosampling. Ferrets administered virus via oronasal and oral routes met euthanasia criteria due to advanced disease 5–10 days post-challenge. Conversely, all ferrets dosed via the ocular route survived until the scheduled study termination 28-day post-challenge. In animals that succumbed to disease, a dose/route response was not observed; increases in disease severity, febrile responses, serum and tissue viral load, alterations in clinical pathology, and gross/histopathology findings were similar between subjects. Disease progression in ferrets challenged via ocular administration was unremarkable throughout the study period. Results from this study further support the ferret as a model for EBOV disease following oral and nasal mucosa exposure.